Clathrin-mediated endocytosis regulates a balance between opposing signals to maintain the pluripotent state of embryonic stem cells - Narayana, V, Yadavalli; Gadgil, Chetan; Mote, Ridim D.; Rajan, Raghav; Subramanyam, Deepa (Stem Cell Reports, 2019)
Endocytosis is implicated in the maintenance of embryonic stem cell (ESC) pluripotency, although its exact role and the identity of molecular players remain poorly understood. Here, we show that the clathrin heavy chain (CLTC), involved in clathrin-mediated endocytosis (CME), is vital for maintaining mouse ESC (mESC) pluripotency. Knockdown of Cltc resulted in a loss of pluripotency accompanied by reduced E-cadherin (E-CAD) levels and increased levels of transforming growth factor beta (TGF-beta) and extracellular signal-regulated kinase (ERK) signaling. We demonstrate that both E-CAD and TGF-beta receptor type 1 (TGF-beta R1) are internalized through CME in mESCs. While E-CAD is recycled, TGF-beta R1 is targeted for lysosomal degradation thus maintaining inverse levels of these molecules. Finally, we show that E-CAD interacts with ERK, and that the decreased pluripotency upon CME loss can be rescued by inhibiting TGF-beta R, MEK, and GSK3 beta, or overexpressing E-CAD. Our results demonstrate that CME is critical for balancing signaling outputs to regulate ESC pluripotency, and possibly cell fate choices in early development.